Self-sensing smart products in smart manufacturing systems. (October 2022) - Lenz, Juergen; MacDonald, Eric; Harik, Ramy; Wuest, Thorsten
Highlights: Paradigm shift for the expanded use of Smart Products spanning middle of life (MOL) and beginning of life (BOL). Discussion of the benefits & opportunities of integrating smart products' capabilities to SMS. Discussion of the barriers & challenges of integrating smart products' capabilities to SMS. Abstract: We are surrounded by a growing number of products with embedded intelligence relying on sensors and internet access. These smart products, that already transform our lives, are also physical entities that need to be manufactured. Manufacturing today similarly relies on data and data-driven insights to improve quality, efficiency, and safety on the shopfloor. This paper discusses the vision to utilize the ability of smart products to sense and communicate already during their own manufacturing to enrich the smart manufacturing system's data for better insights development and optimization. We furthermore, discuss the barriers and opportunities embedded in such a paradigm shift.